2018
DOI: 10.1016/j.jclinepi.2018.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Measurement error is often neglected in medical literature: a systematic review

Abstract: Consequently, it is difficult for readers to judge the robustness of presented results to the existence of measurement error in the majority of publications in high impact journals. Our systematic review highlights the need for increased awareness about the possible impact of covariate measurement error. Additionally, guidance on the use of measurement error correction methods is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 39 publications
(47 reference statements)
0
60
0
Order By: Relevance
“…In most cases, the limiting factor for performing these adjusted analyses will be the availability of quantitative information regarding the measurement error. However, our impression is that even when such quantitative information is available, the adjusted analyses are not being performed …”
Section: Resultsmentioning
confidence: 99%
“…In most cases, the limiting factor for performing these adjusted analyses will be the availability of quantitative information regarding the measurement error. However, our impression is that even when such quantitative information is available, the adjusted analyses are not being performed …”
Section: Resultsmentioning
confidence: 99%
“…28 The use of measurement error corrections is still rare in applied biomedical studies despite an abundance of measurement error problems usually reported as an afterthought to a study. 14,15 Indeed, to our knowledge, no measurement error correction methods have been used so far in the analysis of biomedical trials to correct for measurement error in the endpoint. This may in part be due to a common misconception that measurement error can only affect trial inference by reducing the precision of estimating the effect of treatment and increasing Type-II error, which can be improved by increasing the study sample size.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13] In addition, the application of correction methods for measurement errors in the applied medical literature is unusual. 14,15 We provide an exploration of problems and solutions for measurement error in continuous trial endpoints. For illustration of the problems and solutions for measurement error in continuous endpoints, we consider one published trial that examined the efficacy and tolerability of low-dose iron supplements during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [12] and previous approaches in cataloging methods in high-impact literature [13,14]. Our goals were to (1) document reports of potential misclassification of high risk sexual behaviors in observational studies focusing on sexual minority men and HIV transmission, and (2) characterize the use of bias adjustment methods in correcting the proxies for sexual risk behaviors.…”
Section: Methodsmentioning
confidence: 99%